Poroelastic lamellar metamaterial for sound attenuation in a rectangular duct. (May 2021) - Li, Ke; Nennig, Benoit; Perrey-Debain, Emmanuel; Dauchez, Nicolas
Highlights: A new concept of acoustic metamaterial for duct attenuation is proposed. Using poroelastic lamellas allows easy to tune and manufacture metamaterial. The sensitivity of most parameters is illustrated. A connection between modal veering and best attenuated configuration is shown. Abstract: The sound attenuation of a silencer consisting of a lamella network made with melamine foam inserted in rectangular duct is investigated numerically and experimentally. The lamella arrangement is designed so that skeleton bending elastic resonances appear at low frequency. In addition to this phenomenon, viscothermal losses in the porous material ensure broadband attenuation. The lamella network provides a natural sub-wavelength resonator, without any other kind of inclusions, and create an easy to manufacture metamaterial with high tunability and broadband efficiency. Experimental transmission losses compare well with three dimensional finite element model obtained either on the whole silencer, either on a periodic cell. A parametric study is conducted on the periodic model to identify the effect of different geometrical parameters, like dimensions of the lamella and air gap, as well as physical parameters, like air flow resistivity, elastic modulus and loss factor of the poroelastic material, on the sound attenuation in the silencer.